Taṭbīq Ṭarīqah al-Tamthīl al-Dawrī fī Ta‘līm Mahārah al-Kalām fī al-Madrasah al-Thānawiyyah al-Islāmiyyah al-Ḥukūmiyyah al-Thāniyah Tūlūngāgūng: The Implementation of the Role Play Method in Teaching Speaking Skills at State Islamic Senior High School 2 Tulungagung - Zuyyina Ilmy Azizah; Langgeng Budianto; Yaoping LIU (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2025)
This study aims to address the challenges in improving students' speaking skills at State Islamic Senior High School 2 Tulungagung through the implementation of the Role Play method. The focus of this study is: (1) to describe the implementation of the Role Play method in Arabic language teaching, and (2) to identify the challenges and solutions during the implementation process. This research employs a qualitative descriptive approach with the subject of Arabic language learning using the Role Play method. The data sources include teachers, students, and learning documents. Data were collected through semi-structured interviews, participatory observation, and documentation, and were then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results show that the Role Play method is implemented through stages of providing context, role assignment, dialogue practice, and role performance in the classroom. The teacher acts as a facilitator, while the students actively participate in the role-playing activities. This implementation makes the learning process more dynamic and contextual, and proves effective in improving students' speaking abilities. Keywords: Arabic, Role Play Method, Speaking Skills